2013
DOI: 10.1007/s11745-013-3802-6
|View full text |Cite
|
Sign up to set email alerts
|

Trans Fat Supplementation Increases UV‐Radiation‐Induced Oxidative Damage on Skin of Mice

Abstract: We evaluated the influence of fish oil (FO, rich in n-3 FA), soybean oil (SO, rich in n-6 FA) and hydrogenated vegetable fat (HVF, rich in trans FA) on the oxidative status and viability of skin cells of mice exposed to ultraviolet radiation (UVR). Mice were supplemented with FO, SO or HVF for three months and exposed to UVR (2.72 mJ/cm(2)) for 2 days. One day after the last UVR session, the FO group showed higher levels of n-3 fatty acids (FA), while the HVF showed higher incorporation of trans FA (TFA) in do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 89 publications
3
6
0
2
Order By: Relevance
“…These results are consistent with those reported by Rosenthal and Doloresco , who demonstrated that human skin fibroblasts readily incorporate exogenous free FA into cellular phospholipids and triacylglycerol, facilitating the nutritional modification of cellular composition. In fact, recent studies of our group showed that 90 days of supplementation with SO, fish oil and HVF was sufficient to change the skin FA incorporation in rodents, thus affecting the UVR exposure‐induced damage . Our findings also showed that the MUFA incorporation in the skin of HVF group was higher than that observed in the control group.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…These results are consistent with those reported by Rosenthal and Doloresco , who demonstrated that human skin fibroblasts readily incorporate exogenous free FA into cellular phospholipids and triacylglycerol, facilitating the nutritional modification of cellular composition. In fact, recent studies of our group showed that 90 days of supplementation with SO, fish oil and HVF was sufficient to change the skin FA incorporation in rodents, thus affecting the UVR exposure‐induced damage . Our findings also showed that the MUFA incorporation in the skin of HVF group was higher than that observed in the control group.…”
Section: Discussionsupporting
confidence: 58%
“…SO was used as a control group due to its consumption worldwide and mainly due to its adequate levels of PUFA. The FA profile of each supplemented fat (SO or HVF) and chow was determined as described previously . The experimental supplements were isocaloric in order to prevent metabolic differences between animals, which could cause interferences in the antioxidant defense system .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations